THE IMPACT OF STRATEGIC ALIGNMENT IN ACHIEVING ORGANIZATIONAL SUCCESS-AN EXPLORATORY STUDY OF THE OPINIONS OF A SAMPLE OF EMPLOYEES IN THE SOCIAL PROTECTION AUTHORITY IN BAGHDAD GOVERNORATE - Researcher: Dhiaa M.Taha; Supervision by: A. P. Mohamed I. Taih (Scholars Digest Publishing, 2024)
This research aims to explore the impact of strategic alignment, which includes dimensions such as communication, participation, efficiency, infrastructure, skills, and governance, as an independent explanatory variable in achieving organizational success with its dimensions of effectiveness, organizational culture, effective selection of human resources, and organizational readiness as quick-responsive variables, and given the importance of the research and its significant impact on organizations. Especially in the services sector, the Ministry of Labor and Social Affairs, represented by the Social Protection Authority, was chosen as a field for research. The sample included senior employees at senior and middle levels. Data was collected from a random sample of 160 respondents. The researcher considered the questionnaire as the basic tool for collecting data, and it was analyzed using the best Statistical software (SPSS V.26, Excel V.16, and AOSS). The statistical methods used included measures such as the arithmetic mean, standard deviation, coefficient of variation, simple linear regression, and Pearson correlation coefficient. The main results show that there is a significant positive relationship and causal effect between the research variables, which is what the researcher aims to achieve through his research through data analysis.
Keywords: strategic alignment, organizational success, Social Protection Authority.